Nitrate nitrogen uptake and metabolism in Mikania micrantha stem: insights into enhanced growth and invasiveness - Cai, Minling; Chen, Lihua; Chen, Minghao; Ke, Weiqian; Wang, Dongguang; Peng, Changlian (Frontiers in Plant Science, 2025)
The increasing atmospheric nitrogen deposition, characterized by a rising proportion of nitrate nitrogen (NO3⁻-N), is exacerbating the spread of invasive plant species. Despite this trend, the response mechanisms of Mikania micrantha, a highly invasive plant, to NO3⁻-N remain poorly understood. This study investigates the unique adaptation strategies of M. micrantha to elevated NO3⁻-N levels, providing novel insights into its invasive success under changing nitrogen deposition patterns. Field experiments showed that M. micrantha rhizosphere soil contained higher NO3–N content and protease activity compared to companion plants (Paederia scandens, Ipomoea nil, and Ipomoea cairica). Both roots and stems of M. micrantha had higher NO3–N content and demonstrated stronger nitrogen metabolism capabilities. Pot experiments further showed that increasing NO3⁻-N concentrations (0 mM–40 mM) significantly promoted M. micrantha growth, with optimal phenotypic responses (main stem length, leaf number, branch number, and biomass) observed at 5 mM NO3⁻-N. Nitrogen metabolism enzyme assays revealed that nitrate reductase (NR), nitrite reductase (NiR), glutamate dehydrogenase (GDH), and free amino acid content increased progressively with NO3⁻-N concentration. Transcriptome sequencing and qPCR analyses identified upregulation of key genes related to transcription factors, nitrate transporter-related, nitrogen metabolism enzyme, and amino acid synthesis pathway. These findings demonstrate that M. micrantha employs a multifaceted strategy to exploit elevated NO3⁻-N conditions: enhanced NO3⁻-N uptake from soil, efficient transport to stems, and robust nitrogen metabolism facilitated by coordinated gene expression. This study reveals the adaptation mechanisms of M. micrantha to NO3⁻-N enrichment, offering critical insights for predicting and managing invasive species responses to global atmospheric nitrogen deposition changes. The results highlight the importance of considering nitrogen composition, rather than just quantity, in invasive species management strategies.